Alur Pemikiran Finalisasi Pancasila dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Santika, I Gusti Ngurah; Sujana, I Gede; Kartika, I Made; Suastika, I Nengah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the historical review of the formulation and ratification of the Pancasila and to analyze the flow of thought for the finalization of Pancasila in the 1945 Constitution of the Republic of Indonesia. This study used ideological-historical methods with literature study techniques. The Panitia Sembilan formulated Pancasila's ideology at the Investigative Agency for the Preparatory Work for Independence (BPUPK) meeting on 29 May 1945 to 1 June 1945 and stipulated in the Jakarta Charter on 22 June 1945 and ratified by the Preparatory Committee for Indonesian Independence (PPKI) on 18 August 1945. Finalization of Pancasila in the Constitution The Republic of Indonesia of 1945 was based on the ideological historical experience of the Indonesian nation to maintain national integration by limiting the authority of the People's Consultative Assembly as contained in Article 37 paragraph (1) of the 1945 Constitution of the Republic of Indonesia.This study aimed to describe the historical review of the formulation and ratification of the Pancasila and to analyze the flow of thought for the finalization of Pancasila in the 1945 Constitution of the Republic of Indonesia. This study used ideological-historical methods with literature study techniques. The Panitia Sembilan formulated Pancasila's ideology at the Investigative Agency for the Preparatory Work for Independence (BPUPK) meeting on 29 May 1945 to 1 June 1945 and stipulated in the Jakarta Charter on 22 June 1945 and ratified by the Preparatory Committee for Indonesian Independence (PPKI) on 18 August 1945. Finalization of Pancasila in the Constitution The Republic of Indonesia of 1945 was based on the ideological historical experience of the Indonesian nation to maintain national integration by limiting the authority of the People's Consultative Assembly as contained in Article 37 paragraph (1) of the 1945 Constitution of the Republic of Indonesia.